THE EFFECTIVENESS OF THE USE OF GLASS IONOMER CEMENT "DENTA-CEM" IN COMBINATION WITH DEEP FLUORIDATION WITH THE DRUG "DENTA-FLUO" IN THE TREATMENT OF CARIES BY ATRAUMATIC METHODS - N.I. Djuraeva,; I.Ya. Sadikova,; B.S. Hujamberdiev,; Khakimova Aziza, (Scholar Express Journals, 2021)
The aim of our study was to increase the effectiveness of the treatment of dental caries in "problem" patients using a non-traumatic restorative method using a more economical glass ionomer cement "Denta- Cem" in combination with a deep fluoridation drug Local “Denta-Fluo” from Dentals Pfarma Ltd.
Keywords: Atraumatic restorative treatment; ART-technique; dentophobia; remineralization